Black representation and Information Design: an analysis of the infographic series “Some babies are born black” - Santos Schuelter, Julia; Vassali, Miguel; Teodorico dos Santos, Celio (InfoDesign, 2025)
This article presents an analysis of the infographic series “Some babies are born black” by illustrator Chidiebere Ibe, having as core purpose reflections on information design, Black representation, and contemporary design. To this end, bibliographical reviews were conducted, developing studies on the concepts of information design and Black representation and outlining criteria to understand the construction of the series as a positive case of representation in contemporary design.